The Awareness and Knowledge of Web 2.0 Technologies in Education: An Australian Perspective - Chan She Ping, Christina; Issa, Tomayess (Common Ground Publishing LLC, 2011)
This paper will discuss how Web 2.0 technologies were used in one of the foundation units for the Bachelor Degree of Commerce at Curtin Business School. The research targets undergraduate students, lecturers, and tutors of the Business Information Systems (BIS100) at the School of Information Systems in Curtin University. The research sample size is 122 students for surveys, ten students and seven instructors for interviews. Only 88 students responded to the post-survey. Most universities have already planned, or are currently planning, to change from instructor-delivered teaching to student-facilitated learning with the help of Web 2.0. Because interest has been expressed in the application of Web 2.0 technology in education in some schools, it was deemed worthwhile to carry out further research on the subject. The main purpose of this paper is to investigate the impacts of Web 2.0 technologies on teaching and learning performance at Curtin University, Australia. This research will provide additional information about why Web 2.0 should be adopted in education and will provide several strategies to formulate the adoption of Web 2.0 successfully. The Critical Realism paradigm, which consists of both positivism and interpretive, were applied in the study to explore and understand the relationship between the use of Web 2.0 and the teaching and learning performance. Qualitative and quantitative approaches were used to collect data from surveys and interviews. The results from the post-survey were compared with pre-survey results, to determine any changes in the levels of both awareness and knowledge since the pre-survey. On top of that, face-to-face and email interviews were conducted with students and email interviews with tutors. Significant findings show that the levels of awareness and knowledge of students using Web 2.0 were low at the beginning of the semester, with a slight increase in the levels of awareness and knowledge as the students were exposed to several Web 2.0 tools. In addition, it was noticed that males have more knowledge of Web 2.0 technologies than do females, and are more interested in technology than are females. It was also found that the percentage of students using Web 2.0 to organise group meetings, to communicate with other classmates, and to communicate with their tutors has increased by 6.62%, 7.7%, and 1.82% respectively. Some students found Web 2.0 technologies easy to use and very flexible because they can be easily customised according to users’ requirements, such as Blackboard, the Learning Management System at Curtin University. Web 2.0 tools facilitate easy networking. They help students to more easily collaborate and communicate. Moreover, students do not have to rush to complete, print, and submit assignments to the tutor or lecturer. In regards to teaching, adopting Web 2.0 technology will increase student engagement and it will make classes more interesting and interactive, which may lead to an increase in, creativity, usability, and participation. This technology may encourage better interaction amongst students, and between students and the tutor. However, the Internet is always a necessary part of any work with the Web 2.0 tools. If Web 2.0 tools are used in classes, students may find it difficult to focus and be distracted by other activities such as browsing, chatting, or playing games online. The use of Web 2.0 technology in classes may discourage social interaction, although this depends on how the teacher uses the tools. Further research should be carried out to tackle any disadvantages and challenges of adopting web 2.0 in teaching and learning in Australia and globally.